In Vitro Antioxidant, Antiangiogenic And Vasorelaxant Studies Of Clerodendron Serratum (Spreng.) Leaves Extracts - Mohamed, Ali Jimale (2011)
Clerodendron serratum (Spreng.) leaves from Verbenacea family, locally known as “Timba Tasek” is a traditional Malay medicinal plant used for treating various diseases. However, the present works were focused on evaluating its antiangiogenic, vasorelaxant and antioxidant activities as well as chemical profiles of the leaves extracts. The dried powdered leaves of C. serratum were serially macerated with petroleum ether (a defatting step), chloroform, methanol and water. The antiangiogenic activity (the inhibitory effects of these extracts on blood vessel growth/formation) was studied using rat aortic ring assay. The vasorelaxant activity was studied by examining the inhibitory effect of C. serratum extract on contractile responses of cumulative doses of noradrenaline in isolated rat aortic ring preparation.